Functional screening for anti-CMV biologics identifies a broadly neutralizing epitope of an essential envelope protein - Thomas J. Gardner (Nature Portfolio, 2016)
Human cytomegalovirus (CMV) poses a risk for immunosuppressed patients and newborns, with limited treatment options available. Here, Gardneret al. use a high-throughput approach and identify monoclonal antibodies that bind a highly conserved domain in the viral glycoprotein gH as potent inhibitors of CMV infection.